The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1590/s0100-879x1999000400018
|View full text |Cite
|
Sign up to set email alerts
|

Axotomy increases NADPH-diaphorase activity in the dorsal root ganglia and lumbar spinal cord of the turtle Trachemys dorbigni

Abstract: Seven days after transection of the sciatic nerve NADPH-diaphorase activity increased in the small and medium neurons of the dorsal root ganglia of the turtle. However, this increase was observed only in medium neurons for up to 90 days. At this time a bilateral increase of NADPH-diaphorase staining was observed in all areas and neuronal types of the dorsal horn, and in positive motoneurons in the lumbar spinal cord, ipsilateral to the lesion. A similar increase was also demonstrable in spinal glial and endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The possibility of colocalization of CB with TH, NOS, and ChAT was suggested by the distribution of these proteins in the spinal cord of turtles (Brü ning et al, 1994;Kiehn et al, 1992;Luthman et al, 1991;Partata et al, 1999;Powers and Reiner, 1993;Radmilovich et al, 1997). The analysis of these colocalizations is of importance in the comparative scope insofar as different degrees of colocalization were found in the few species studied (Fahandejsaadi et al, 2004;Gamboa-Esteves et al, 2001;Morona et al, 2006a,b).…”
Section: Colocalization Of Cb With Th Nos and Chatmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of colocalization of CB with TH, NOS, and ChAT was suggested by the distribution of these proteins in the spinal cord of turtles (Brü ning et al, 1994;Kiehn et al, 1992;Luthman et al, 1991;Partata et al, 1999;Powers and Reiner, 1993;Radmilovich et al, 1997). The analysis of these colocalizations is of importance in the comparative scope insofar as different degrees of colocalization were found in the few species studied (Fahandejsaadi et al, 2004;Gamboa-Esteves et al, 2001;Morona et al, 2006a,b).…”
Section: Colocalization Of Cb With Th Nos and Chatmentioning
confidence: 99%
“…In addition, to further characterize the CBir cell populations in the turtle spinal cord, double immunohistochemistry was used to study colocalization of CB with nitric oxide synthase (NOS), choline acetyltransferase (ChAT), and TH. This last set of experiments was prompted by the observation in previous studies that these markers were also found in similar neuronal populations of the spinal cord of turtles (Brü ning et al, 1994;Kiehn et al, 1992;Luthman et al, 1991;Partata et al, 1999;Powers and Reiner, 1993;Radmilovich et al, 1997;Smeets and Gonzá lez, 2000) and colocalization was found or suggested in the human, rat, lizard, and anuran spinal cord (Fahandejsaadi et al, 2004;Gamboa-Esteves et al, 2001;Grkovic and Anderson, 1997;Morona et al, 2006a,b).…”
Section: Introductionmentioning
confidence: 98%